Manfaat Intervensi Acceptance and Commitment Therapy dalam Menurunkan Kecemasan dan Perilaku Adiktif pada Pasien NAPZA - Lilik Sulistiyowati; Budi Anna Keliat; Giur Hargiatna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the benefits of Acceptance and Commitment Therapy interventions in reducing anxiety and addictive behavior in drug patients. The method used is a systematic review through article searches adjusted for the formulation of research questions with the PICO formula in the Clinicalkey for Nursing, ScienceDirect, EMBASE, Scopus, and EBSCOhost databases. The results showed that the Acceptance and Commitment Therapy intervention was able to effectively reduce anxiety and addictive behavior in drug patients. In conclusion, the Acceptance and Commitment Therapy intervention can reduce anxiety and addictive behavior in drug patients. Keywords: Acceptance and Commitment Therapy, Anxiety, Drugs